Psikoedukasi Mengenai Peran Dzikir Dalam Kesejahtraan Psikologis Individu Di SMAN 1 Banda Baro - Anastasya, Yara Andita; Harun, Nurlaila; Nisaq, Saidatun; Salsabila, Hanisa; Chairunnisa, Aura; Nur, Alia; Ayunda, Dira (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
Early adulthood is a complex and crucial developmental phase, marked by significant changes in physical, cognitive, emotional and social aspects. In this phase, mental health becomes an important issue with a fairly high prevalence of disorders such as anxiety, depression and stress. This research explores the role of dhikr (remembering Allah) in improving individual well-being in early adulthood. Dhikr, as a spiritual practice in Islam, has psychological benefits such as calming the soul, reducing stress and anxiety, increasing spiritual closeness, concentration, mental health, gratitude, and strengthening social relationships. Through psychoeducation, students are enthusiastic and motivated to implement dhikr in their daily lives in order to achieve better mental and mental well-being. The research results show that dhikr has great potential in facilitating positive development and mental health in individuals in early adulthood.